2015
DOI: 10.1074/jbc.m115.662817
|View full text |Cite|
|
Sign up to set email alerts
|

Ac2PIM-responsive miR-150 and miR-143 Target Receptor-interacting Protein Kinase 2 and Transforming Growth Factor Beta-activated Kinase 1 to Suppress NOD2-induced Immunomodulators

Abstract: Background: Ac 2 PIM signals via TLR2 to direct both pro-and anti-inflammatory responses. Results: Ac 2 PIM induces miR-150/143 via SRC-FAK-PYK2-CREB-P300 signaling to target RIP2 and TAK1 and subdues MDPstimulated PI3K-PKC-MAPK-␤-catenin axis. Conclusion: Ac 2 PIM-mediated TLR2 signaling suppresses the NOD2-induced immunomodulators viz. COX-2, SOCS-3, and MMP-9. Significance: TLR2-NOD2 crosstalk accentuated the utilities of Ac 2 PIM and MDP as vaccine adjuvant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…S3 . The MAPK/ERK pathway is intimately linked to the altered miRNAs seen in nodular SGC and it is possible that these miRNAs are acting as tumour suppressors to inhibit this pathway 26 , 27 . Moreover, synthetic miR-143 has been shown to silence KRAS signalling including its effector signalling molecules AKT and ERK (MAPK1).…”
Section: Resultsmentioning
confidence: 99%
“…S3 . The MAPK/ERK pathway is intimately linked to the altered miRNAs seen in nodular SGC and it is possible that these miRNAs are acting as tumour suppressors to inhibit this pathway 26 , 27 . Moreover, synthetic miR-143 has been shown to silence KRAS signalling including its effector signalling molecules AKT and ERK (MAPK1).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the P300 protein may activate transcription by binding to transcription factors; thus, P300 is also known as a transcriptional coacti-vator ( 34 36 ). Previous studies have demonstrated that miR-150 regulates the expression of the transcriptional co-activator P300 ( 37 , 38 ). Accordingly, the present study identified that P300 was a downstream target of MIAT/miR-150-5p.…”
Section: Discussionmentioning
confidence: 99%
“…and transforming growth factor β-activated kinase 1 (TAK1), which are the mediators of the NOD2 signaling pathway, and applying their inhibitory effect on the inflammation process (Prakhar et al, 2015). are the other miRNAs that are associated with NOD2 and are involved in the pathogenesis of IBD, especially Crohn's disease (Brain et al, 2013;Chuang, Chuang, Zhai, Wu, & Kwon, 2013;Ghorpade, Sinha, Holla, Singh, & Balaji, 2013).…”
Section: Nucleotide Oligomerization Domains Toll-like Receptors and Mmentioning
confidence: 99%